Is multimodality therapy necessary for the management of pure myxoid liposarcomas? A multi‐institutional series of pure myxoid liposarcomas of the extremities and torso. Issue 2 (12th September 2014) - Baxter, Katherine J.; Govsyeyev, Nicholas; Namm, Jukes P.; Gonzalez, Ricardo J.; Roggin, Kevin K.; Cardona, Kenneth
<x xml:space="preserve">Abstract</x> Background and Objectives The treatment of patients with pure (<5% round cell component) myxoid liposarcomas (pMLS) has not been well characterized. We hypothesized that multimodality therapy (oncological resection with radiation therapy) may not be necessary for pMLS. Methods Patients who underwent resection of localized pMLS at three institutions from 2000 to 2010 were identified and treatment variables were analyzed. Results Of 75pts with pMLS, the median tumor size was 10 cm, the majority (95%) were deep tumors, and located in lower extremity. Radiation (XRT) was administered to 58pts(77%). Comparing the no XRT to XRT patients, lower extremity location (77% vs. 79%, P = 1.0), tumor size (13 vs. 11 cm, P = 0.3), and positive margins (13% vs. 16%, P = 1.0) were similar. The majority (82%) of patients not receiving XRT had deep tumors. After a median follow‐up of 60 months, 2pts (3%) developed local recurrence and 10pts (13%) developed distant recurrence with a mean recurrence‐free survival (RFS) and disease‐specific survival (DSS) of 114 and 148mos, respectively. In multivariate analyses, increasing age and tumor size were the only significant predictors of recurrence. XRT was not a significant predictor of RFS in multivariate analysis. Conclusions pMLS is an STS subtype with favorable tumor biology and an extremely low‐rate of local recurrence. Our results suggest that multimodality therapy may not be necessary for all pMLS. J. Surg. Oncol. 2015 111:146–151. © 2014 Wiley Periodicals, Inc.